Personhood, ethics, and animal cognition situating animals in Hare's two level utilitarianism - Varner, Gary E. (Gary Edward), 1957- (New York ; Oxford : Oxford University Press, 2012)
Drawing heavily on recent empirical research to update R.M. Hare's two-level utilitarianism and expand Hare's treatment of 'intuitive level rules,' Gary Varner considers in detail the theory's application to animals while arguing that Hare should have recognized a hierarchy of persons, near-persons, and the merely sentient.
Description based on online resource; title from PDF title page (viewed on Aug. 24, 2012).
Includes bibliographical references and index.
Keywords: Animal rights; Cognition in animals; Ethics; Utilitarianism; Hare, R. M